Electrophoretic Elucidation and Determination of Stability Constants of Some Binary Metal Complexes [M-Penicillamine-System] - KUMAR PANDEY, ASHISH; SINGH, SATYENDRA (Asian Journal of Chemistry, 2010)
A new method involving the use of paper electrophoresis is described for the study of equilibria in metal-ligand complex system in solution. The technique is based on the movement of metal ion under an electric field with the complexants added to the background electrolyte the stability constants of the complex were found to be log k1 =14.53 (for Th(IV)); log k1 = 13.38, log k2 = 5.42 (for Fe(III)) ; log k1 =12.80, log k2 = 4.04 (for Cr(III)); log k1 = 12.10, log k2 = 3.21 (For Al(III)); complexes at 35º and ionic strength 0.1 M.